NEW RECORD OF SEI WHALE, BALAENOPTERA BOREALIS LESS FROM INDIAN WATERS - Venkataraman, G; Dorairaj, K; Devaraj, M; Ganapathi, R (Indian Journal of Fisheries, 2011)
The stranding of a 15.53 metres long sei w4iale, Balaenoptera borealis for tlie first time in the Indian shores is reported and described